Replication Studies in Economics: How Many and Which Papers Are Chosen for Replication, and Why? - Frank Müller-Langer; Benedikt Fecher; Dietmar Harhoff; Gert G. Wagner (European Commission, Joint Research Centre (JRC), 2018)
We investigate how often replication studies are published in empirical economics and what types of journal articles are eventually replicated. We find that from 1974 to 2014 0.10% of publications in the Top 50 economics journals were replications. We take into account the results of replication (negating or reinforcing) and the extent of replication: narrow replication studies are typically devoted to mere replication of prior work while scientific replication studies provide a broader analysis. We find evidence that higher-impact articles and articles by authors from leading institutions are more likely to be subject to published replication studies whereas the probability of published replications is lower for articles that appeared in higher-ranked journals. Our analysis also suggests that mandatory data disclosure policies may have a positive effect on the incidence of replication.
Keywords: A1; B4; C12; C13; 330; Replication; economics of science; science policy; economic methodology